On the drive of modes by ICRF accelerated ions in a tokamak - L.-G. Eriksson; F. Porcelli (Nuclear Fusion)
Energetic ions have the potential to drive instabilities with toroidal mode number $n_{φ} = 0$ in tokamak fusion plasmas. A necessary condition is that their distribution function is either anisotropic or exhibits a region of phase space with a positive slope in the energy direction (so-called ‘bump-on-tail’ distribution). Here an exploration of both possibilities is presented for Ion Cyclotron Range of Frequency (ICRF) accelerated energetic ions. It is found that ion cyclotron resonance layers placed on the high-field side of the magnetic axis provide the most conducive conditions for the drive of vertical $n_{φ} = 0$ modes. We also discuss to what extent sawtooth redistribution of the ICRF accelerated ions can transiently lead to distribution functions that are locally inverted in the energy direction. However, the latter effect appears to be less efficient in driving $n_{φ} = 0$ vertical modes than velocity space anisotropy for high-field-side resonances.